Analisis Kesuksesan Learning Management System (LMS) Menggunakan Model ISSM Pada PT. XYZ - Rasyidin, Reghi Givansa; Faroqi, Asif; Wulansari, Anita (Dinasti Review, 2023)
The use of the Learning Management System (LMS) is one form of technological advancement in the field of education used by PT. XYZ, where PT. XYZ provides a learning platform using this method. The Learning Management System method, which is considered a one-way learning method, raises issues where users can only access learning materials in the form of videos but cannot interact with the instructors, making it impossible for users to ask questions related to the material provided. This has an impact on users who are deemed not to be maximizing their understanding and ability to answer questions related to the given material. This research aims to explore the factors of the effectiveness of the Learning Management System at PT. XYZ based on the DeLone and McLean (DLML) model. The research method used in this study is quantitative. The results of this research are that the factors that most influence the success of the Learning Management System are User Satisfaction and Net Benefits, where these two indicators are influenced by System Quality, Information Quality, and Service Quality. The results of the hypothesis testing indicate that these factors have a positive influence, especially on User Satisfaction with the Learning Management System, which is the Net Benefit. This is supported by the results of the hypothesis testing, which show that the original sample has the highest value for the User Satisfaction variable compared to other variables.